KENDALA PENGGUNAAN APLIKASI PEMBELAJARAN DARING SMAN 4 TANJUNG JABUNG TIMUR DI TENGAH PANDEMI COVID-19 - Darma Darmawati Wati; Rahmanelli Rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims to find out what applications students and teachers use during online learning, how and what are the obstacles for students in using these online learning applications and provide efforts that can reduce the impact of these constraints. As we know the Covid-19 pandemic continues to hit Indonesia which has an impact on the world of education which makes online learning continue to apply in various regions to reduce and prevent the spread of Covid-19 itself. This research was conducted at SMAN 4 Tanjung Jabung Timur, the population of this study were all class XI science and social studies as well as educators. Samples were taken randomly as many as 51 students using the Slovin method. The results found in this study are, 1). The application used by students and teachers during online learning is WhatsApp Group (WAG). 2) The problems faced by students during online learning were the internet network, data packages and the availability of smartphones, and the main obstacle was the inadequate network. 3) efforts that can be made, namely by submitting assignments directly to schools on condition that they continue to follow health protocols. Keywords: Constraints, Online Learning, Covid-19.